The Effects of Day Care on Health During Childhood: Evidence by Age - Gerard J. van den Berg; Bettina M. Siflinger (Institute of Labor Economics (IZA), 2018)
This paper studies the effects of day care exposure on behavioral disorders and mental and physical health at various ages during childhood. We draw on a unique set of merged population register data from Sweden over the period 1999-2008. This includes merged information at the individual level from the inpatient and outpatient registers, the population register and the income tax register. The outpatient register contains all ambulatory care contacts including all contacts with physicians and therapists. Visits are recorded by day, and comprehensive diagnoses are recorded for each visit. By exploiting variation in day care exposure by age generated by a major day care policy reform, we estimate cumulative and instantaneous effects on child health at different ages. We find a positive cumulative impact on behavior at primary school ages, in particular for children from low socio-economic status households, and substitution of infections from primary school ages to low ages. All this affects health care utilization and leads to a moderate reduction in health care costs. Results are confirmed by analyses based on a sibling design and on regional and household-specific components of day care fees.
Keywords: I12; J13; J14; C23; C25; C83; 330; child care; pre-school; infections; non-cognitive ability; behavioral disorders; illness; education; health registers; day-care fees